(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
This study examined the decadal analysis and estimation of temperature changes in northern senatorial zone of Kaduna state-Nigeria. Temperature data (minimum and maximum) covering 1967 to 2016 was obtained from the archives of Nigeria Meteorological Agency (NiMet) station Zaria. These data were used to determine the decadal trends and estimate changes in minimum, maximum and average temperatures using trend analysis in Microsoft excel tool (2013) and SPSS 23.0 version. Findings indicate a total increase in average temperature of 1.72°C at the rate of 0.034°C year-1. For the maximum temperature, a total increase of 1.68°C at the rate of 0.033°C year-1 and for minimum temperature an increase of 1.72°C the rate of 0.0340C year-1, indicating increased warming in recent years. The result of Cramer’s test for the monthly average temperature analysis indicated that the tk values for the last two decades shows an increase in temperature as indicated by their positive with the months of March, April, may, June, July, August, September and October being significantly warmer at 95% confidence level than the long-term condition. The paper concludes that the study area is getting warmer in recent years. The paper recommends that government should come up with policies that will help in. managing socio- economic consequences of rising temperature and /or planned interventions to avoid surprises and take right decision in case of unexpected periods of intense heat. Additional functioning synoptic weather stations should be provided to complement the existing one since the study area is becoming hotter in recent years.